The Glengarry Highland Games, 1948-2003: Problematizing the Role of Tourism, Scottish Cultural Institutions, and the Cultivation of Nostalgia in the Construction of Identities - Mason, Courtney (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
In the midst of dynamic socio-economic and cultural conditions, the Glengarry Highland Games were revived in a rural community of Eastern Ontario in 1948. Throughout the second half of the 20th century, this festival became the lifeblood of a movement perpetuating Scottish Highland cultural practices and (re)producing "Scottishness" as the dominant cultural currency in an ethnically diverse county. Using primary evidence in the forms of oral histories, newspapers, and archives, this paper examines how the expansion of spaces and opportunities to celebrate Scottish cultural practices has influenced the social construction of regional and cultural identities in Glengarry County from 1948 to the 21st century.